A synopsis of Byrsonima (Malpighiaceae) in Roraima state, northern Brazil - Rodrigues, Rodrigo Schütz; Bartsch, Gleiceanny Rosas; Flores, Andréia Silva (Phytotaxa, 2020)
Byrsonima is the second largest genus of Malpighiaceae with approximately 130 species, of which ca. 100 species occur in Brazil. Despite its economic and ecological importance, the genus has not been comprehensively studied in Roraima, the northernmost state in Brazil. Here we present a taxonomic synopsis for the species of Byrsonima from Roraima, with an identification key, illustrations, and comments on morphology, habitat, and geographical distribution. Of the 19 species occurring in Roraima, three are recorded for the first time for the state (B. arthropoda, B. densa, and B. fernandezii). Also, one species is endemic (B. delicatula, recently described), and two (B. chalcophylla and B. schomburgkiana) occur in Brazil only in the state of Roraima.